Hemodynamic alterations and their clinical implications in the vertebrobasilar system among patients with isolated posterior circulation ischemic vertigo - Song, Xuhua; Liang, Jingwei; Tian, Congzhe (Frontiers in Neurology, 2024)
BackgroundThis research aimed to ascertain independent risk factors and the diagnostic value of vascular parameters in differentiating posterior circulation ischemic isolated vertigo (PCI-IV) from vestibular peripheral vertigo (VPV).MethodsThis study involved 247 patients with acute-onset vertigo, categorized into two groups: PCI-IV and VPV. Multivariate logistic regression was conducted to pinpoint independent risk factors for PCI-IV.ResultsThe duration of vertigo, particularly episodes lasting more than a few hours, was a significant predictor of PCI-IV (OR = 2.183, p < 0.001). The presence of diabetes mellitus (OR = 1.746, p = 0.008) and hypertension (OR = 2.291, p = 0.004) also notably increased the likelihood of PCI-IV. Hemodynamic measurements such as the inner diameter and average blood flow velocity (Vmean) of the vertebral artery, as well as the resistive index (RI), were identified as significant predictive factors (p ≤ 0.033). The ROC analysis demonstrated the vertebral artery RI had the highest diagnostic accuracy with an area under the curve (AUC) of 0.78, indicating an optimal balance between sensitivity and specificity.ConclusionClinical features such as the duration of vertigo, diabetes mellitus, and hypertension, along with vascular hemodynamics, are crucial in assessing the risk of PCI-IV. The RI in the vertebral artery emerged as a particularly potent diagnostic parameter. These findings advocate a multifaceted diagnostic approach, combining clinical and vascular parameters for the effective identification and management of PCI-IV.